A Study On E-Banking Services In Kurdistan Regional Banks With Special Reference To Cihan Bank - Khalifa, Farah Basher; Basariya, S. Rabiyathul (International Journal of Psychosocial Rehabilitation, 2020)
E-Banking as the rush of things to come, gives a heavy advantage to all the shoppers as far as expense of exchanges either through the web, mobile or any other electronic conveyance channels. E-Banking is currently broadly rehearsed in Kurdistan region. There are different kinds of e-keeping money administrations like SMS managing an account, Tele Banking, Push and Pull administrations, ATM, Fast Track and so forth that have been presented by the business banks in Kurdistan region. This examination endeavors to investigate different structures and attributes of e-keeping money and discovers the benefits and faults of e-managing an account in chosen business banks of our nation. The significant discoveries of the examination demonstrate that all the business banks chose for the investigation have been rehearsing e-keeping money effectively and CIHAN banks in Kurdistan region is giving electronic managing an account benefits more successfully than other business banks chose in this investigation. Plus, there is a positive effect of e-putting money on the financial advancement in Kurdistan region. There ought to be enhancement of such exercises in country territories of Iraq.